Use of Ovitrap for The Spatial Mapping of Aedes spp. in The Endemic Area of Dengue Fever of Baitussalam District Aceh Besar - Elita Agustina; Muhajirin Muhajirin; Muhammad Iqbal Arif (Universitas Islam Negeri Ar-Raniry, 2024)
The strategy for controlling dengue vector through periodic monitoring is an effective mitigation effort. Periodic monitoring of dengue vectors is generally more often conducted in the larval stage rather than the egg stage. Monitoring Aedes eggs periodically using ovitraps is more effective because it is not restricted by season. The objective of this study is to conduct spatial mapping of Aedes spp. distribution using ovitraps in Baitussalam Subdistrict, Aceh Besar. This study used observational methods and purposive sampling to determine the sample houses for ovitrap placement. A total of 50 houses in 5 gampong/village were observed. Analysis was conducted using the GPS Essentials application and Google Earth Pro software. The results showed that there were 4 gampong with Aedes spp. egg distribution in Baitussalam Subdistrict, Aceh Besar, namely Gampong Blang Krueng, Gampong Baet, Gampong Kajhu, and Gampong Cadek, while in Gampong Lam Ujong, no ovitraps positive for Aedes eggs. Ovitraps are an effective method for mapping Aedes spp. in efforts to control dengue. Keyword: Aedes spp; Dengue fever; ovitrap; spatial mapping.